Alcohol and cocaine use prior to suspected suicide: Insights from toxicology. (14th March 2021) - Bailey, James; Kalk, Nicola J.; Andrews, Rebecca; Yates, Sarah; Nahar, Limon; Kelleher, Michael; Paterson, Susan
Abstract: Introduction: This study investigates whether there is a relationship between alcohol and cocaine use in deaths where suicide by self‐injury is the suspected cause of death. Methods: Adults referred by coroners to the Imperial College London Toxicology Unit for toxicological analysis between 2012 and 2016 were reviewed for inclusion criteria. Those who died by self‐injury reasoned to be deliberate were included in the analysis. Femoral blood alcohol concentration (BAC) and presence of cocaine or benzoylecognine (a metabolite of cocaine) in blood and/or urine were tabulated and odds ratios calculated. Results: A total of 1722 decedents met inclusion criteria. BAC was ≥50 mg/dL in 29% of decedents. Cocaine was detected in 8.4% of cases. The likelihood of testing positive for cocaine increased with BAC and was most frequent between 100 and 199 mg/dL, consistent with moderate to severe intoxication (odds ratio 5.88, 95% confidence interval 3.80, 9.09; P ≤ 0.001) compared to those with BAC <10 mg/dL. Discussion and Conclusions: This study demonstrates a correlation between increasing BAC and likelihood of cocaine use prior to suspected suicide, up to a level consistent with severe intoxication. Cocaine use was found in a high proportion of cases relative to the general population reporting regular use. This pattern of drug and alcohol use has previously been given little attention in suicide prevention strategies and clinical prioritisation.